Lifelong learning and transfer of psychosocial attributes across adult sport: can we move beyond youth sport?. Issue 2 (4th May 2022) - Santos, Fernando; Callary, Bettina
ABSTRACT: Throughout the last decades, many researchers have devoted their time to understanding how sport can foster positive psychosocial attributes, such as life skills development and transfer in various youth sport settings. In this paper, we conduct a narrative review focused on coaches' contributions to athletes' psychosocial development across HP and Masters sport, as well as expand on future research directions and provide practical implications. In the first section, we focus on coaching practice and psychosocial development within HP sport. In the second section, we outline the nuances of coaching approaches for psychosocial development within Masters sport. In the last section, we provide directions for future research in this field and emphasise the need for lifelong learning and transfer of psychosocial attributes across adult sport.